The Relationship of The School Chairman’s Duties As A Supervisor With The Teacher’s Understanding In Developing The Learning Plan In Public High School 3 Sekayu - Samsilayurni Samsilayurni; Hadiwinarto Hadiwinarto (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Relationship of The School Chairman’s Duties As A Supervisor With The Teacher’s Understanding In Developing The Learning Plan In Public High School 3 SekayuOne of the tasks in teaching is to make learning tools, but there are still teachers in schools who do not understand how to prepare lesson plans and sometimes find it difficult to develop lesson plans components. This study aims to determine the relationship between the principal's duties as supervisors and the understanding of teachers in the preparation of lesson plans at SMA Negeri 3 Sekayu. The population in this study were 30 teachers, so that all of them were used as research samples. The quantitative descriptive method is applied using a questionnaire instrument. Based on the results of hypothesis testing, it shows that there is a significant relationship between the duties of the principal as a supervisor and the understanding of the teacher in preparing RPP SMA Negeri 3 Sekayu. With the correlation value of person or rcount, namely 0.656> r table, namely 0.361 with a significant level of 5%. So it can be concluded that there is a relationship between the principal's duties as supervisors and the teacher's understanding in preparing RPP at SMA Negeri 3 Sekayu. Suggestions to school principals and teachers to continue to improve understanding in lesson planning (RPP).Abstract: Hubungan Tugas Ketua Sekolah Sebagai Pengawas Dengan Pemahaman Guru Dalam Menyusun Rencana Pembelajaran Di SMA Negeri 3 SekayuSalah satu tugas dalam mengajar adalah membuat perangkat pembelajaran, tetapi masih ada guru di sekolah yang belum memahami cara menyusun RPP dan terkadang merasa kesulitan untuk mengembangkan komponen RPP. Penelitian ini bertujuan untuk mengetahui hubungan tugas kepala sekolah sebagai pengawas dengan pemahaman guru dalam penyusunan RPP di SMA Negeri 3 Sekayu. Populasi dalam penelitian ini adalah 30 guru, sehingga semuanya dijadikan sampel penelitian. Metode Deskriptif Kuantitatif diterapkan dengan menggunakan instrumen angket. Berdasarkan hasil uji hipotesis menunjukkan bahwa terdapat hubungan yang signifikan antara tugas kepala sekolah sebagai pengawas dengan pemahaman guru dalam menyusun RPP SMA Negeri 3 Sekayu. Dengan nilai korelasi person atau rhitung yaitu 0,656> rtabel yaitu 0,361 dengan taraf signifikan 5%. Sehingga dapat disimpulkan bahwa terdapat hubungan antara tugas kepala sekolah sebagai pengawas dengan pemahaman guru dalam penyusunan RPP di SMA Negeri 3 Sekayu. Saran kepada kepala sekolah dan guru agar terus meningkatkan pemahaman dalam penyusunan rencana pelajaran (RPP).